Upaya Mengurangi Resiko Bencana di Pedesaan dengan Memanfaatkan Citra Penginderaan Jauh - Rahmad Rahmad; M. Uliah S; Hairuddin Hairuddin; A. Miftahul U; M. Arifin; Adnan Adnan (Fakultas Teknik Universitas Cenderawasih, 2024)
The natural disaster is one of the phenomena that can occur at any time, anywhere and anytime. The most common disasters are floods, landslides, tornadoes and earthquakes, which can cause damage, loss of life and even loss of life. The conditions of Tabaroge Village and its surroundings are prone to flooding geographically, geologically, hydrologically and demographically. The condition of the East Luwu Regency area is at the confluence of several earth tectonic plates. Therefore, most of the potential disaster threats are in the Tabaroge Village area and its surroundings. Based on the occurrence of natural disasters in East Luwu Regency in recent years, which occurred in several villages. Judging from the characteristics of the Tabaroge Village area, Efforts to Reduce Disaster Risk in Rural Areas by Utilising Remote Sensing Imagery aims to provide information on locations that have disaster risk. This research uses the analysis methods of Standardised Precipitation Index (SPI), Normalised Difference Vegetation Index (NDVI), Normalised Difference Water Index (NDWI), Soil Adjusted Vegetation Index (SAVI) and Inverse Distance Weighted (IDW) for data exploration using Arcmap (GIS). In future development, it is expected to be able to implement disaster risk reduction by utilising remote sensing imagery in Tabaroge Village, East Luwu Regency.